-1k-6k=10-5k

Simple and best practice solution for -1k-6k=10-5k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1k-6k=10-5k equation:


Simplifying
-1k + -6k = 10 + -5k

Combine like terms: -1k + -6k = -7k
-7k = 10 + -5k

Solving
-7k = 10 + -5k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '5k' to each side of the equation.
-7k + 5k = 10 + -5k + 5k

Combine like terms: -7k + 5k = -2k
-2k = 10 + -5k + 5k

Combine like terms: -5k + 5k = 0
-2k = 10 + 0
-2k = 10

Divide each side by '-2'.
k = -5

Simplifying
k = -5

See similar equations:

| 8y-26=-74+2y | | 4(a-7)+8=2(a-5) | | y=10x+90 | | x+17/15=-14/15 | | 8x-8y=48 | | 6m-3=-15m | | 8x+24y=16 | | 0x+0y=15 | | 6m-3=15m | | -11-6a=1a-4 | | 3/5-8(8.8) | | 8y-26=-64+2y | | 2*x^3-3*x^2-36*x+5=0 | | 2z-28=8+8z | | .07*x=84 | | 5x-12=-17 | | 11/3*-7/2*4/5-x | | 3(a-1)=-17 | | 2*x^3-2*x^2-36*x+5=0 | | 0=121p^2-100 | | m*(-4/5)=2,23 | | 4(3x+4x)-1=91 | | .5z-1=-13 | | 7-2Inx=3 | | 800x-0.55=400x+0.45 | | f(x)=9x^2+4x+9 | | 2(j-4)=10 | | 2*16+46=x | | 2*16+46= | | x^2-cx-6c^2=0 | | 5x^10-8x^7= | | .66c+6=18 |

Equations solver categories